2022
DOI: 10.1113/jp282933
|View full text |Cite
|
Sign up to set email alerts
|

Action potential amplitude and baroreflex resetting of action potential clusters mediate hypoxia‐induced sympathetic long‐term facilitation

Abstract: Columbia Okanagan in Canada and is mentored by Dr Glen Foster. She is currently investigating neurovascular reflex regulation of arterial blood pressure in response to homeostatic disturbances in oxygen tension. In the future, she aims to continue her research on sympathetic discharge properties and blood pressure governing mechanisms, particularly as it pertains to hypertension development in patients with obstructive sleep apnoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 50 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…Average values presented in the current study in Table 1 are similar but do not duplicate those reported previously (Shafer et al., 2022), due to differences in sample size and the longer analysis periods (7 min vs . 5 min in Shafer et al., 2022) required to investigate the effects of sympathetic AP activity on sympathetic transduction of MAP. Written informed consent was obtained from all participants.…”
Section: Methodssupporting
confidence: 66%
See 4 more Smart Citations
“…Average values presented in the current study in Table 1 are similar but do not duplicate those reported previously (Shafer et al., 2022), due to differences in sample size and the longer analysis periods (7 min vs . 5 min in Shafer et al., 2022) required to investigate the effects of sympathetic AP activity on sympathetic transduction of MAP. Written informed consent was obtained from all participants.…”
Section: Methodssupporting
confidence: 66%
“…Hypoxia‐induced chemoreflex activation elicits an increase in sympathetic outflow to the skeletal muscle vasculature, which remains elevated even when blood gases return to normal (Foster et al., 2010; Jouett et al., 2017; Ott et al., 2020; Querido et al., 2010, 2011; Shafer et al., 2021, 2022; Steele, Skow et al., 2021; Stuckless et al., 2020; Vermeulen et al., 2020; Xie et al., 2001). Sympathoexcitation during and following hypoxia appears to be mediated by a resetting of the baroreflex to higher operating points (Cooper et al., 2005; Halliwill et al., 2003; Querido et al., 2011; Shafer et al., 2022; Tremblay et al., 2016). Interestingly, parallel changes in vascular resistance are not observed (Morgan et al., 1995; Steele, Skow, et al., 2021; Tamisier et al., 2004), suggesting that the transduction of sympathetic activity may be attenuated during room air recovery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations